Mapping And Evaluating The Impact Of Land Subsidence In Semarang (Indonesia) - Irwan Gumilar; Hasanuddin Z. Abidin; Teguh P. Sidiq; H. Andreas; R. Maiyudi; M. Gamal; Y. Fukuda (Indonesian Journal of Geospatial, 2013)
Abstract. Semarang is the capital of Central Java province, located in the northern coast of Java island, Indonesia. Land subsidence in Semarang has been widely reported and its impacts can be seen already in daily life. Based on the estimation from Levelling, Interferometric Synthetic Aperture Radar (InSAR), Microgravity and Global Positioning System (GPS) survey methods, land subsidence with rates of up to about 19 cm/year were observed during the period of 1999 up to 2011. Results derived from GPS since 2008 up to 2011 show that land subsidence in Semarang has spatial and temporal variations, with spatial average rates of about 6 to 7 cm/year.Based on the site visit surveys, the impacts of land subsidence can be seen in several forms such as cracks in buildings, damage of infrastructure (road and bridges), tilting and damaged houses, and wider expansion of coastal flooding (tidal flooding). Tidal flooding and tilting and damaged houses frequently occurs in the area where the subsidence rate is high (northern part of Semarang). Cracks in buildings and damage of infrastructure (road and bridges) occur in the boundary of large subsidence area and the less. Keywords : GPS , land subsidence, damages, coastal flooding, Semarang